Associations between a new day 4 embryo grading system and implantation rates in frozen embryo transfer (FET) cycles. Issue 42 (16th October 2020) - Li, Hongxing; Xu, Xiaojuan; Jing, Yuanxue; Liu, Ling; Wang, Yiqing
Abstract : Abstract: The purpose of this study is to present a new day 4 (D4) embryo grading system for the assessment of embryos in frozen-thawed embryo transfer (FET) cycles. A new grading system (grades A–E) was modified from the 2011 ESHRE Istanbul Consensus for D4 embryos in FET cycles. In total, we retrospectively analyzed 5640 embryos with known implantation data after D4 transfer in FET cycles by using this proposed grading model. The transferred embryos exhibited a similar declining trend in implantation rates from the top grade A to the lowest grade E. The implantation rates of grade B and E embryos in the in vitro fertilization group were significantly higher than that in the intracytoplasmic sperm injection group (grade B: 41.82%, 35.23%, χ 2 = 5.85, P < .05 and grade E: 18.53%, 14.81, χ 2 = 76.86, P < .01, respectively). The receiver operating characteristic analysis showed that our proposed model predicted the implantation outcomes of all embryos (area under the ROC curve = 0.65; 95% CI, 0.63–0.66; P < .01). This study demonstrated that the new grading system provided by us turned out to be a useful tool in assisting embryo selection via embryo morphological changes, and D4 embryo transfer provided a simple and applicable method for a daily routine in FET cycles.